2009
DOI: 10.1111/j.1365-2141.2009.07699.x
|View full text |Cite
|
Sign up to set email alerts
|

Beta2‐microglobulin is a better predictor of treatment‐free survival in patients with chronic lymphocytic leukaemia if adjusted according to glomerular filtration rate

Abstract: Summary Even in the era of newer and sophisticated prognostic markers, beta2‐microglobulin (B2M) remains a simple but very powerful predictor of treatment‐free survival (TFS) and overall survival (OS) in patients with chronic lymphocytic leukaemia (CLL). However, B2M levels are heavily influenced by the patient’s glomerular filtration rate (GFR) and this study aimed to evaluate whether GFR‐adjusted B2M (GFR‐B2M) had improved prognostic value compared to unadjusted B2M in a cohort of over 450 consecutive CLL pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 20 publications
(26 reference statements)
1
24
0
Order By: Relevance
“…It has been reported that B2-microglobulin is a good prognostic marker of inflammation, and has a strong predictive role in CLL patients [10]. It also proved to be a good prognostic marker in our patients, as the OS at 4 years was 95% when the B2-microglobulin was normal, compared to a 4 year OS of 76% in the cases with elevated levels (HR: 0.275, 95%CI: 0.061-1.244, p=0,03) (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that B2-microglobulin is a good prognostic marker of inflammation, and has a strong predictive role in CLL patients [10]. It also proved to be a good prognostic marker in our patients, as the OS at 4 years was 95% when the B2-microglobulin was normal, compared to a 4 year OS of 76% in the cases with elevated levels (HR: 0.275, 95%CI: 0.061-1.244, p=0,03) (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with a creatinine clearance of less than 30 mL/min were excluded from this trial so it is unlikely that high β-2M levels reflected poor renal function. 19 Previous studies have shown that β-2M is a predictor of progressive disease, progression-free survival and overall survival. [20][21][22] However this is the first study to show that this simple, readily available and inexpensive assay retains prognostic significance even in models that include a comprehensive range of demographic and biological risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the last decades, the aim of therapy for patients with CLL has shifted from palliation 2 to disease eradication, particularly for younger patients who account for almost a third of the entire population with this disease. 3 Moreover, we are now able to predict the outcome of these patients more accurately using a plethora of prognostic markers such as molecular cytogenetics; 4 point mutations in a variety of genes, including TP53, NOTCH1, SF3B1 and POT1; [5][6][7][8][9] DNA methylation, 10 immunoglobulin heavy chain gene (IGHV) mutational status; 11,12 CD38 and ZAP-70 expression; 12,13 serum β 2 -microglobulin levels; 14 and clinical stage; 15,16 all of which have a significant impact on time to first treatment, overall survival, treatmentfree survival or progression-free survival after therapy.…”
Section: Introductionmentioning
confidence: 99%